Strategi Komunikasi Publik Humas Pemerintah Kabupaten Sidoarjo dalam Meningkatkan Reputasi Di Masyarakat - Ismojo Herdono; Dzaki Makarim (LPPM Stikosa-AWS, 2023)
The Regent of Sidoarjo, Muhdlor Ali, of course, so that the reputation of Sidoarjo Regency is seen as good by the community, it requires the role of public relations. Public relations has a role, among others, as a bridge or liaison between internal and external parties. This study aims to determine the public relations strategy of the Government of Sidoarjo Regency in improving reputation in the community. The theory used is communication strategy, public communication, public relations, and reputation. According to Rogers as quoted by Hafied Cangara, communication strategy can be interpreted as a plan that is built with the aim of changing human behavior in large numbers through the transfer of new ideas. Public communication can be interpreted as exchanging information or messages with several people who are inside or outside an organization, either directly or indirectly. The method used in this research is a quasi-qualitative research method, namely an approach that is not purely qualitative or not yet qualitative in essence because in its form this approach is still influenced by the habits of a quantitative approach. Data collection techniques and research methods in this study are divided into two, namely regarding interviews, and data from documentation. While the validity of the data is done through triangulation of sources. The results of this study show that the Sidoarjo Regency Government Public Relations communication strategy is through external, internal, vertical, horizontal and diagonal communication. The activities carried out by the Public Relations of the Sidoarjo Regency Government through the utilization and use of media to disseminate information to the public, the quality of human resources, and the formation of a reputation were not optimal. In order to realize the Public Relations objective of the Sidoarjo Regency Government in improving reputation in the community, it requires active use of both mass and social media, improving the quality of human resources, and coordination between agencies.